2019
DOI: 10.1002/best.201800094
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der Wassersättigung auf die statische und dynamische Druckfestigkeit von Beton

Abstract: Untersucht wurde der Einfluss der Wassersättigung auf die statische und dynamische Druckfestigkeit von Beton. Hierzu wurden zwei verschiedene Probengeometrien mit definierten Sättigungsgraden getestet. Für die dynamischen Druckfestigkeitsversuche wurde der Split‐Hopkinson‐Bar verwendet. Es wurde festgestellt, dass die Druckfestigkeit von Beton mit steigendem Sättigungsgrad abnimmt, sowohl im statischen als auch im dynamischen Belastungsfall. Der Betrag der Abminderung der Druckfestigkeit mit steigender Sättigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
3
6
1
2
Order By: Relevance
“…Studies based on defined saturation levels on concrete and mortar specimens were first carried out by Zhou et al 27,28 The static and dynamic compressive strength decreases with increasing saturation, but increases slightly again for nearly fully saturated concrete specimens. These results were confirmed by Mosig and Curbach 29,30 in experimental test series. It was found that the geometry of the specimens influences the strength decrease due to water saturation.…”
Section: Introductionsupporting
confidence: 78%
“…Studies based on defined saturation levels on concrete and mortar specimens were first carried out by Zhou et al 27,28 The static and dynamic compressive strength decreases with increasing saturation, but increases slightly again for nearly fully saturated concrete specimens. These results were confirmed by Mosig and Curbach 29,30 in experimental test series. It was found that the geometry of the specimens influences the strength decrease due to water saturation.…”
Section: Introductionsupporting
confidence: 78%
“…Die statische und dynamische Druckfestigkeit sinkt mit zunehmender Sättigung, steigt jedoch bei nahezu voll gesättigten Betonproben wieder leicht an. Diese Ergebnisse konnten von Mosig und Curbach [30, 31] in experimentellen Versuchsreihen bestätigt werden. Sie stellten außerdem fest, dass die Geometrie der Proben den Festigkeitsabfall infolge der Wassersättigung beeinflusst.…”
Section: Introductionunclassified
“…The influence of moisture on the strength reduction of UHPC is consistent with the literature. [21][22][23] Why the effect between water storage and climate chamber storage is changed in HPC could not be clarified within the scope of these investigations. In principle, however, when comparing the dry samples for both concretes, it can be assumed that one reason for the earlier failure with increasing temperature is the pore water pressure.…”
Section: Discussionmentioning
confidence: 99%